Basal cell carcinoma-clinico-pathological study in Eastern India in correlation with different risk factors - Chetan Jain; Neha Garg; Sulekha Singh; Sarbani Chattopadhyay (Wolters Kluwer Medknow Publications, 2022)
Objectives: To study the histological variants and mimickers of basal cell carcinoma (BCC) alongwith different risk factors among a group of patients from eastern India. Methods: The specimen for the study was sent by the dermatology department for histopathology after skin biopsy. Results: Out of 42 patients, 15 patients studied were males and the rest of the cases were females. The male to female ratio was 0.55:1. Maximum (15 cases) cases were in the age group of 50-59 years. Apart from sunlight, chronic arsenic exposure is an important risk factor of BCC. Basal cell hyperplasia and squamous cell carcinoma are the histological differential diagnosis of nodular BCC and basosquamous BCC. Conclusion: BCC is a disease of the older age group and with female preponderance in our study. Nodular basal cell carcinoma was the most common histologic type of basal cell carcinoma. The face was the most common site for BCC followed by the scalp. UV radiations and Arsenic do play role in the pathogenesis of BCC. CD10 helps differentiate superficial BCC from basal cell hyperplasia.